Alien woody plant invasions in natural forests across China. (31st March 2021) - Wang, Yupin; Fei, Songlin; Tang, Zhiyao; Sun, Yuanfeng; Chen, Guoping; Wang, Xiangping; Wang, Shaopeng; Fang, Jingyun
Abstract: Aims: Alien plant invasion has become a major global environmental issue, causing severe economic and ecological damages. Severe invasions have been reported in some regions of China. However, most studies have been conducted at local and provincial levels, and the overall degree of invasion in natural forests across China remains unclear. Here, we explored the biogeographic patterns and their environmental and socioeconomic controls of the invaded alien woody plants in natural forests across the country. Methods: We compiled the data of 3573 natural forest plots across the mainland China and mapped spatial distribution of alien woody plant invasion. We also used logistic regression models to identify the key socioeconomic and environmental factors that were associated with the observed invasion patterns. Important Findings: We found that only 271 plots among 3573 natural forest plots were invaded by alien woody plants, accounting for 7.58% of all plots. Among all 2825 woody plant species across all plots surveyed, only 5 alien species (0.177%) were found. Both human activities and climate factors were related to the observed invasion patterns. Since China's natural forests are mostly located in remote mountainous areas with limited human disturbance, alien woody plant invasions are less than those reported in North America and Europe. However, with the development of transportation and increased economic activities in mountainous areas, more invasions by alien plants may be expected in the future. Therefore, proactive management and policy making are desired to prevent or slow down the invasion processes.